Has the wage Phillips curve changed in the euro area? - Guido Bulligan; Eliana Viviano (IZA Journal of Labor Policy, 2017)
Increasing evidence shows that in the aftermath of the global financial crisis, in the euro area, the relationship between price inflation and economic slack became stronger. Instead, there is no clear evidence of a strong(er) relationship between wage inflation and unemployment. In this paper, we estimate a Phillips curve with time-varying coefficients separately for Italy, Spain, Germany and France and we find that, with the exception of Germany, after the global financial crisis, the sensitivity of hourly wage changes to labour market slack increased. Second, by the use of administrative microdata, available only for Italy, we relate daily wage changes to the local unemployment rate. The results confirm the steepening of the Phillips curve after 2008, also when controlling for composition effects.
Keywords: E24; E31; E58; 330; Wage growth; Phillips curve; Parameter instability